​​Negotiating Hospitality in Pat Mora's "Bilingual Christmas" and Sandra Cisneros's "It Occurs to Me I Am the Creative/Destructive Goddess Coatlicue" - Méliné Kasparian (Lectora: Revista de Dones i Textualitat)
This article explores the link between hospitality and power in two poems by contemporary Chicana writers Pat Mora and Sandra Cisneros, reflecting on how these two poems denounce the complicity of certain discourses and practices of hospitality with oppression and exclusion. Both poems explore the intersection between hospitality, power and inequality, highlighting the power differentials at play beneath relationships of hospitality. Hospitality appears in the two poems as a cover-up for marginalization and exploitation, the exclusion of migrants and post-migrants and the subjugation of women through norms of self-sacrifice. However, the two poems also reclaim hospitality and offer textual forms of generosity and care, or poetic hospitality in the way they welcome in voices, readers, and stories.